The Perpetuation of Psychological Wounds: A Comprehensive Review of Intergenerational Trauma in Indian Patriarchal Society - Rhea; Sangeeta Kakkar (International Journal of Trends in Humanities, 2025)
The transmission of trauma effects from one generation to the next is known as intergenerational trauma, and it is particularly common in patriarchal civilisations such as India. Laws, economy, and social conventions are shaped by patriarchy, a societal framework that primarily gives males power, authority, and advantages. This perpetuates gender inequity and marginalises women. Aim: The purpose of this review is to examine how trauma is transmitted throughout generations in India, with a particular emphasis on the interaction between trauma and patriarchal systems. The review included previous research from Google Scholar and PubMed that was published during the previous 15 years. Results: Through the prism of historical trauma, the article analyses both minor traumas, such as emotional abuse within families, and big traumas, such as forced migration during the 1947 Partition. It also looks into how patriarchal standards normalise gender-based violence, which worsens psychological injury and feeds the trauma cycle for decades. The review covers a number of trauma transmission mechanisms, such as genetics, family, and psychological elements. It draws attention to the ways that sociocultural factors fuel psychological suffering, health inequities, and enduring dysfunctional parenting styles. To treat trauma, the review finds culturally sensitive coping mechanisms and healing techniques, such as contemporary psychotherapies and customary rituals. To support healing and resilience among populations impacted by intergenerational trauma, a comprehensive strategy that takes into account individual, family, and societal aspects is crucial.
Keywords: Epigenetic mechanisms; Gender inequality; Intergenerational trauma; cultural healing practices; patriarchal societies